Underwater surface electromyography for the evaluation of muscle activity during front crawl swimming: A systematic review - Kwok, W. Y.; So, B. C. L.; Ng, S. M. S. (Journal of Sports Science & Medicine, 2023)
This systematic review is aimed to provide an up-to-date summary and review on the use of surface electromyography (sEMG) in evaluating front crawl (FC) swim performance. Several online databases were searched by different combinations of selected keywords, in total 1956 articles were retrieved, and each article was assessed by a 10-item quality checklist. 16 articles were eligible to be included in this study, and most of the articles were evaluating the muscle activity about the swimming phases and focused on assessing the upper limbs muscles, only few studies have assessed the performance in starts and turns phases. Insufficient information about these two phases despite the critical contribution on final swimming time. Also, with the contribution roles of legs and trunk muscles in swimming performance, more research should be conducted to explore the overall muscle activation pattern and their roles on swimming performance. Moreover, more detailed description in participants` characteristics and more investigations of bilateral muscle activity and the asymmetrical effects on relevant biomechanical performance are recommended. Lastly, with increasing attention about the effects of muscles co-activation on swimming performance, more in-depth investigations on this topic are also highly recommended, for evaluating its influence on swimmers.